The moderating role of two learning related behaviours in preschool children's academic outcomes: learning behaviour and executive function. Issue 1 (2nd January 2022) - Beisly, Amber; Kwon, Kyong-Ah; Jeon, Shinyoung; Lim, Chaehyun
ABSTRACT: Executive function and learning behaviour play an important role in children's academic outcomes by helping them maintain attention, work cooperatively, and stay focused, especially for those from lower family socioeconomic status (SES) backgrounds. This study explored whether these learning-related skills were associated with children's concurrent math and literacy skills and whether they moderated the associations of family SES with math and literacy skills. Preschool children (n = 179) from early childhood education settings were directly assessed on executive function, math, and literacy skills. Executive function and learning behaviour were significantly correlated with children's math and literacy outcomes. Learning behavior moderated the association between family SES and child math outcomes. Teachers may support learning behaviour by teaching active listening and frustration management techniques, thus motivating children to actively participate in learning. This serves to buffer the negative impacts of family SES on children's academic outcomes, specifically math skills.